Pleasures and perils : girls' sexuality in a Caribbean consumer culture - Curtis, Debra, 1963- (Rutgers series in childhood studies., 2009)
Pleasures and Perils follows a group of young girls living on Nevis, an island society in the Eastern Caribbean. In this provocative ethnography, Debra Curtis examines their sexuality in gripping detail: why do Nevisian girls engage in sexual activity at such young ages? Where is the line between coercion and consent? How does a desire for wealth affect a girl's sexual practices?. Curtis shows that girls are often caught between conflicting discourses of Christian teachings about chastity, public health cautions about safe sex, and media enticements about consumer delights. Sexuality's contrad.